Exploring Smoking Stigma, Alternative Tobacco Product Use, & Quit Attempts - Brown-Johnson, Cati G. (Health Behav Policy Rev, 2016)
OBJECTIVES: Investigate smoking stigma among different tobacco user types. METHODS: US adults (N=1,812) responded to an online survey, including non-smokers, smokeless tobacco users, exclusive smokers, and smokeless and cigarette “dual users”. RESULTS: Dual users perceived the highest smoking stigma. Stigma was higher for smokers open to quitting by switching to smokeless. E-cigarette users (smokers) reported higher stigma than non-users. Making a past-year quit attempt was predicted by smoking stigma, and smokeless and/or e-cigarette use. CONCLUSIONS: Smoking stigma and dual use of smokeless tobacco and/or e-cigarettes with cigarettes predict quit attempts. However, smoking stigma might prevent smokers from consulting doctors and induce use of alternative tobacco products as cessation aids.